Sustainable Upgrade of Post-Consumer PLA: The Effect of Adding a Plasticizer and a Chain Extender on the Functional Properties and Toxicity of This Recycled Bioplastic - Velasquez, E (American Chemical Society, 2026)
The environmental risks associated with the use of petroleum-based plastics are well known, and therefore, the use of biopolymers has boomed in recent years. Polylactic acid (PLA) stands out as a great alternative, and although PLA is compostable, its recycling is considered a sustainable approach to manage its residues and promote a circular economy. The aim of this work was to investigate the final properties of post-consumer recycled PLA (rPLA) after the addition of different additives. Post-consumer PLA-based plastics were obtained after a simulation of service life and recycling processes of commercial PLA-based water bottles, and subsequently, different composites including a plasticizer and a chain extender (CE) were obtained by melt extrusion. Significant changes were observed in the structural and thermal parameters of the composites, including their crystallinity, when these additives were incorporated. However, the water vapor permeability values were not significantly different from that of control rPLA. In terms of overall migration, the values obtained for samples containing CE were well below the established limit, although samples containing plasticizers showed quite high values. Cytotoxicity assays in intestinal cells indicated that only composites with the highest plasticizer content exhibited slight toxicity at the intestinal barrier. Overall, contrasting roles were identified for the two additives: the plasticizer enhanced the flexibility but led to increased migration values, whereas the CE improved stability and reduced the migration risk. These results demonstrated that modifying post-consumer rPLA with suitable additives can improve its physical properties while maintaining safety, thus offering a practical and sustainable approach to its use in food packaging applications.